2022
DOI: 10.3389/fendo.2022.849794
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Metformin as an Adjuvant Therapy for Infertile Women With Endometrial Complex Hyperplasia/Complex Atypical Hyperplasia and Their Subsequent Assisted Reproductive Technology Outcomes

Abstract: ObjectiveTo investigate the adjuvant efficacy of metformin treatment to achieve pathological complete response (CR) in patients with endometrial complex hyperplasia (CH) and complex atypical hyperplasia (CAH), and secondarily, to evaluate their pregnancy outcomes after following assisted reproductive technology (ART).Study DesignThis prospective cohort study analyzed 219 patients diagnosed with infertility and CH/CAH from January 2016 to December 2020. Among these patients, 138 were assigned to the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Among the 13 studies, 1 study was presented as a conference in 2020 ( 19 ), and finally as an article in 2023 ( 20 ), and 5 studies enrolled both patients with EH and patients with EEC ( 19 24 ), and 5 studies focused only on patients with EH ( 8 , 11 , 12 , 25 , 26 ), and 2 studies enrolled only patients with EEC ( 9 , 10 ). Six studies were prospective trials ( 9 , 11 , 12 , 23 , 26 , 27 ), while seven were retrospective trials ( 8 , 10 , 19 22 , 24 , 25 ). The study published by Matsuo et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 13 studies, 1 study was presented as a conference in 2020 ( 19 ), and finally as an article in 2023 ( 20 ), and 5 studies enrolled both patients with EH and patients with EEC ( 19 24 ), and 5 studies focused only on patients with EH ( 8 , 11 , 12 , 25 , 26 ), and 2 studies enrolled only patients with EEC ( 9 , 10 ). Six studies were prospective trials ( 9 , 11 , 12 , 23 , 26 , 27 ), while seven were retrospective trials ( 8 , 10 , 19 22 , 24 , 25 ). The study published by Matsuo et al.…”
Section: Resultsmentioning
confidence: 99%
“…There are two routes of progestin therapy, with systemic administration including oral medroxyprogesterone acetate, megestrol acetate, norethindrone, depo-medroxyprogesterone acetate, and local administration via a levonorgestrel-releasing intrauterine device. The route of progestin therapy were systemic administration in eight studies ( 8 , 12 , 19 , 20 , 22 24 , 26 ), and local administration alone in two studies ( 11 , 27 ), and systemic administration combined with local administration in one studies ( 10 ), and systemic or local administration in two studies ( 21 , 25 ). The dose of metformin was administered in a range from 500 mg/d ( 21 ) to 2,500 mg/d ( 20 , 25 ), with the commonly administered dose of 1,000 mg/d and 1,500 mg/d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin, in addition to its role as an antidiabetic agent, has garnered attention for its potential anticancer properties in several neoplasia [152][153][154][155][156], although the mechanisms underlying its anticancer effects are not fully understood [26]. Preclinical studies using in vitro and in vivo models have provided valuable insights: metformin might inhibit cell proliferation [157] by inducing cell cycle arrest [158], and promoting apoptosis [159] through the AMP-activated protein kinase (AMPK) pathway [160], the mammalian target of rapamycin (mTOR) pathway [157], and the insulin-like growth factor (IGF) signalling pathway [161].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…All this clinical evidence indicated that Met had a certain ability to regulate sex steroid hormone profiles. In addition, clinical trials have also proven that Met can improve endometrial hyperplasia (EH), endometrial cancer (EC), bladder cancer, prostate cancer (PCa), and so on [ [13] , [14] , [15] ]. Related preclinical studies have shown that Met inhibits cellular proliferation and blocks the cell cycle in the G0/G1 stage of atypical EH and endometrioid EC and PCa cell lines, resulting in its antiproliferative effect [ 16 ].…”
Section: Introductionmentioning
confidence: 99%